2013
DOI: 10.1590/s1676-06032013000300001
|View full text |Cite
|
Sign up to set email alerts
|

The coexistence of endemic species of Astyanax(Teleostei: Characidae) is propitiated by ecomorphological and trophic variations

Abstract: The coexistence of endemic species of Astyanax (Teleostei: Characidae) is propitiated by ecomorphological and trophic variations. Biota Neotrop. 13(3): http://www.biotaneotropica.org.br/v13n3/en/abstract?article+bn00513032013Abstract: The aim of the present study was to evaluate factors that may favor the coexistence of three endemic species of Astyanax (Astyanax bifasciatus, Astyanax minor and Astyanax gymnodontus ) in Segredo Reservoir (Iguaçu River, Paraná State, Brazil), and to test the hypothesis that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
6
19
0
Order By: Relevance
“…This study confirmed that Astyanax species are an opportunistic group (Mise et al., ) with the ability to exploit a wide variety of trophic resources; however, some important differences were found between the two coexisting species studied here. For example, δ 15 N and δ 13 C showed wider variation in A. aeneus (Figure ), which has been suggested as a characteristic of fish with omnivorous habits in lacustrine systems (Córdova‐Tapia, Contreras, & Zambrano, ; Jepsen & Winemiller, ; Vander Zanden & Vadeboncoeur, ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study confirmed that Astyanax species are an opportunistic group (Mise et al., ) with the ability to exploit a wide variety of trophic resources; however, some important differences were found between the two coexisting species studied here. For example, δ 15 N and δ 13 C showed wider variation in A. aeneus (Figure ), which has been suggested as a characteristic of fish with omnivorous habits in lacustrine systems (Córdova‐Tapia, Contreras, & Zambrano, ; Jepsen & Winemiller, ; Vander Zanden & Vadeboncoeur, ).…”
Section: Discussionsupporting
confidence: 90%
“…In characiforms, previous studies have found correlations between ecomorphological traits and trophic ecology, which can help us to understand the factors that enable the coexistence of closely related species (Bonato et al., ; Mise et al., ). The present study corroborated the occurrence of a significant correlation between ecomorphological traits and trophic habits (i.e., stable isotopes values) of two sympatric species of Astyanax genus.…”
Section: Discussionmentioning
confidence: 99%
“…If such associations gain phylogenetic support, i.e., if phylogenetically unrelated species exhibit convergence and related species exhibit morphological divergences, the hypothesis gains considerable power of inference (Wainwright & Reilly, 1994). Several studies have shown consistent relationships between morphology and feeding habits (Pouilly et al, 2003;Oliveira et al, 2010;Pagotto et al, 2011;Mise et al, 2013), demonstrating different predictive models of community structure (Casatti & Castro, 2006;Oliveira et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Small‐sized, pelagic, opportunistic, with generalist habits and moving in shoals ( Astyanax spp. ; Cassemiro et al ., ; Loureiro‐Crippa and Hahn, ; Mise et al ., ), as much as benthic species, with narrower feeding habits, that occupy lentic stretches ( Glanidium ribeiroi ; Pimelodus britskii ; Reis et al ., ), large‐bodied species, which lives near to the substrate, rarely organized in shoals ( Hypostomus commersoni ; Reis et al ., ) and also exclusive fish‐eating predators ( Oligosarcus longirostris ; Gealh and Hahn, ), showed an increase in abundance after the water level variation.…”
Section: Discussionmentioning
confidence: 99%